Isolation of Aerobic Bacteria from Surgical Site Infection and their Antibiotic Susceptibility Pattern (Bangladesh Journal of Infectious Diseases, 2017)
Background: Surgical site infection is one of the commonest complications after surgical intervention. Source of wound infections may be exogenous or endogenous. Wound swabs culture is the most frequently used method for confirming the diagnosis of surgical site infection. A regular bacteriological review is necessary to identify the causative agents and their antibiotic susceptibility pattern.Objective: The purpose of the present study was to find out the aerobic bacteria from wound swabs culture and their antibiotic susceptibility pattern.Methodology: A total of 175 wound swabs sample were collected aseptically from surgical site infection during the study period. Standard bacteriological methods were used for isolation and identification of organisms and their susceptibility pattern.Results: A total of 175 wound swab samples were collected from surgery departments. Out of 175 samples 102 (58.28%) were positive by culture. Among the isolated organisms the gram negative bacilli were predominant 67 (65.68%) than the gram positive cocci 35 (34.32%).The most common isolated bacteria were Escherichia.coli 30(29.41%) followed by Staphylococcus aureus 28 (27.45%) Pseudomonous areuginosa 20(29.85%), Acinetobacter spp 08(11.94%), Coaggulase negative Staphylococcus (CONS) 07(6.86%) Klebsiella pneumoniae 05(4.90%), Proteus spp 03(4.45%), and Citobacter spp 01(1.49%). Among the total 175 samples 114(65.14%) were collected from male patients and 61(34.86%) were from female patients. All the isolated gram negative bacilli showed resistant to all antibiotics and all isolated gram positive cocci were resistant to all antibiotics except Linezolid. Among the isolated Staphylococcus aureus 8 (24.85%) were MRSA and one (3.57%) were VRSA. The most effective antibiotics were Amikacin, Meropenem, Imipenem and Tazobactam in this study.Conclusion: Surgical site infections remain the commonest post operative complications after surgery and one of the commonest encountered hospital acquired infections. Therefore, periodic review needs be done to find out the causative agents and their antibiotic susceptibility pattern for better treatment and managementBangladesh Journal of Infectious Disease 2015;2(2):28-32